2017
DOI: 10.1016/j.ijpharm.2016.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gastrointestinal variables affecting drug and formulation behavior: Methodologies, challenges and opportunities

Abstract: (2017) Exploring gastrointestinal variables affecting drug and formulation behavior: methodologies, challenges and opportunities. International Journal of Pharmaceutics, 519 (1-2). pp. 79-97. ISSN 1873-3476Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/39960/1/FinalVersion-Revised-FOR_EPRINTS_1_YEAR_EMBARGO_ELSEVIER.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 158 publications
2
40
0
Order By: Relevance
“…The in vitro solubility data also provided a foundation for the hypothesis that food may not affect ribociclib absorption, further supported by PBPK models for ribociclib, which were constructed and validated with clinical data from healthy volunteers and patients with cancer. Sensitivity analyses based on PBPK models of ribociclib absorption built into both the GastroPlus and Simcyp software packages showed that exposure was independent of gastric pH over the physiologic range (pH range, 1.0–8.0), consistent with the lack of impact of pH on the in vitro solubility of ribociclib in the biorelevant media. This hypothesis was then tested and confirmed by the food effect study in healthy volunteers, which showed that ribociclib PK parameters were similar in the fed or fasted state.…”
Section: Discussionmentioning
confidence: 80%
“…The in vitro solubility data also provided a foundation for the hypothesis that food may not affect ribociclib absorption, further supported by PBPK models for ribociclib, which were constructed and validated with clinical data from healthy volunteers and patients with cancer. Sensitivity analyses based on PBPK models of ribociclib absorption built into both the GastroPlus and Simcyp software packages showed that exposure was independent of gastric pH over the physiologic range (pH range, 1.0–8.0), consistent with the lack of impact of pH on the in vitro solubility of ribociclib in the biorelevant media. This hypothesis was then tested and confirmed by the food effect study in healthy volunteers, which showed that ribociclib PK parameters were similar in the fed or fasted state.…”
Section: Discussionmentioning
confidence: 80%
“…2,3 However, intestinal permeability is more complex than generally recognized; for example, drug permeability is location dependent and may vary in each point throughout the GIT. 4,5 The mechanisms behind this segmental-dependent permeability phenomenon include variations in the expression level of different transporters (e.g., P-glycoprotein [P-gp]), pH changes along the GIT, varying water content in different intestinal segments, 6,7 different morphologies and mucosal cell differentiation along the GIT, and so forth. 1,[8][9][10][11][12][13] For instance, upward expression pattern was shown for P-gp along the small intestine (SI), while the opposite trend was shown for MRP2, resulting in segmentaldependent drug permeability.…”
Section: Introductionmentioning
confidence: 99%
“…In the areas where current science does not allow establishing bioequivalence without in vivo studies based on the BCS (e.g., low solubility immediate‐release formulations of class II and IV, class III products with formulation difference and modified‐release products), the improvement of in vitro and modeling and simulation tools is important. Specific gaps that the GDUFA Regulatory Science research program aims to fill include direct measurement of drug concentration in the gastrointestinal (GI) tract, the role of excipients in altering drug absorption, the impact of drug release rates on metabolite formation, research into hydrodynamics and colon physiology to improve prediction of modified‐release product formulations, predictive in vitro dissolution methods, and research related to solid or amorphous dispersion of low solubility drugs . These examples are cases in which the interaction between formulation properties and GI physiological factors are critical to the prediction of in vivo product performance.…”
Section: Bioequivalence Of Orally Administered Drugsmentioning
confidence: 99%